2009
DOI: 10.1002/mus.21404
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis—Evolutionary and other perspectives

Abstract: In this study some particular and puzzling aspects of amyotrophic lateral sclerosis (ALS) are discussed, with an emphasis on the role of neocortical evolution. Other issues explored include the nature of the clinical deficit in ALS; anatomical and evolutionary aspects of the neocortex, motor cortex, and corpus callosum; and some discussion as to when ALS begins. In common with other neurodegenerative diseases, ALS may result from dysfunctional neocortical circuitry. It is suggested that the disease starts some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 113 publications
(95 reference statements)
4
52
0
Order By: Relevance
“…Specifi cally, our data corroborate the recent concept of the CC as a conduit for the spread of pathology from one hemisphere to the other (47). In agreement with our fi ndings, several clinical studies have demonstrated an impaired interhemispheric inhibition in ALS even at an early stage of disease progression, which could be mediated by CC impairment and associated with detection of mirror movements (48,49).…”
Section: Discussionsupporting
confidence: 93%
“…Specifi cally, our data corroborate the recent concept of the CC as a conduit for the spread of pathology from one hemisphere to the other (47). In agreement with our fi ndings, several clinical studies have demonstrated an impaired interhemispheric inhibition in ALS even at an early stage of disease progression, which could be mediated by CC impairment and associated with detection of mirror movements (48,49).…”
Section: Discussionsupporting
confidence: 93%
“…Notwithstanding a need for dedicated studies in cases of pure PMA as well as in the earliest stages of typical ALS, we speculate, like others, 30 that ALS may be fundamentally a cortical neurodegenerative disorder. Rapid increase in human lifespan may have exposed a vulnerability of the aging brain for the specialized motor functions that have evolved on the basis of much shorter survival.…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 52%
“…Hypotheses about focality of onset and spread of disease in ALS have indirectly implicated the CC (see figure in reference 13), and others have speculated that the CC might be a "conduit" for pathologic spread within a corticomotoneuronal model of ALS. 30 Although asymmetry of symptom onset is poorly understood, the observation of concordance for handedness and laterality of upper limb onset in ALS may provide further indirect support for an independent cortical vulnerability, when considered alongside studies that have noted greater cortical excitability and altered cerebral activation patterns in the dominant vs nondominant hand. 31 It is clear also that ALS pathology extends beyond the CST, sharing pathologic as well as clinical features with some forms of frontotemporal dementia (FTD).…”
Section: Figure 2 Regional Fractional Anisotropy (Fa) Reductions and mentioning
confidence: 99%
“…There is evidence for greater connectivity in the dominant motor cortex with respect to handedness10; specifically, it has been noted that the production of movements in dominant and non-dominant hands involves distinct cerebral networks 11. Evolutionary aspects of neocortical function might have relevance to ALS pathogenesis, in that humans have evolved uniquely complex levels of corticomotoneuronal organisation and connectivity as part of the switch to bipedal locomotion and particularly the development of fine hand control through an opposable thumb 12. Such complexity may have come at a price and harbour a vulnerability in the ageing motor system unmasked by ALS.…”
Section: Discussionmentioning
confidence: 99%